1994
DOI: 10.1016/s0006-3495(94)80665-4
|View full text |Cite
|
Sign up to set email alerts
|

Chicken skeletal muscle ryanodine receptor isoforms: ion channel properties

Abstract: To define the roles of the alpha- and beta-ryanodine receptor (RyR) (sarcoplasmic reticulum Ca2+ release channel) isoforms expressed in chicken skeletal muscles, we investigated the ion channel properties of these proteins in lipid bilayers. alpha- and beta RyRs embody Ca2+ channels with similar conductances (792, 453, and 118 pS for K+, Cs+ and Ca2+) and selectivities (PCa2+/PK+ = 7.4), but the two channels have different gating properties. alpha RyR channels switch between two gating modes, which differ in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
80
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 64 publications
17
80
2
Order By: Relevance
“…Similar results were obtained from SR vesicles of toadfish white swimming muscles by O'Brien et al [19]. Percival et al [23] investigated the ion channel properties of c~-and [3-RyRs partially purified from SR of chicken skeletal muscle and reported that the two isoforms embodied Ca 2+ channels with similar conductances but different gating properties on activation by Ca 2+ and ATP, and on inactivation by Ca 2+. Thus these investigators have concluded that the two RyR isoforms in nonmammalian skeletal muscles have distinct CICR properties, in contrast to our conclusion.…”
Section: Z Murayama E Ogawalfebs Letters 380 (1996) 267-271supporting
confidence: 70%
See 3 more Smart Citations
“…Similar results were obtained from SR vesicles of toadfish white swimming muscles by O'Brien et al [19]. Percival et al [23] investigated the ion channel properties of c~-and [3-RyRs partially purified from SR of chicken skeletal muscle and reported that the two isoforms embodied Ca 2+ channels with similar conductances but different gating properties on activation by Ca 2+ and ATP, and on inactivation by Ca 2+. Thus these investigators have concluded that the two RyR isoforms in nonmammalian skeletal muscles have distinct CICR properties, in contrast to our conclusion.…”
Section: Z Murayama E Ogawalfebs Letters 380 (1996) 267-271supporting
confidence: 70%
“…in the absence and presence of AMPOPCP and/or caffeine [3,22]. Our conclusion that the two isoforms are equally potent as CICR channels is at variance with the speculation that [3-RyR may serve as a CICR channel that amplifies Ca 2+ release [19,23]. However, the possibility that the dihydropyridine receptor or some other component(s) in vivo may modulate the channel activities of RyR remains to be confirmed.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This third pattern of calcium modulation has not been described in any tissue. One ryanodine receptor isoform that is expressed in chicken skeletal muscle shows modal behavior, with low and high Po modes [28]. However, the low Po channels never showed eo > 0.1 in continuous records lasting up to 20 min, making it unlikely that the low Po values found are due to modal channel behavior.…”
Section: Referencesmentioning
confidence: 94%